Non-halogenated recovery method of intracellular polyhydroxyalkanoates from local isolate Comamonas sp. EB172 - Mohammadi, Mitra (2012)
In this study, the use of NaOH treatment and chemical-free aqueous solution for intracellular polyhydroxyalkanoates (PHAs) recovery from local isolate Gram-negative wild type bacteria Comamonas sp. EB172 at different NaOH concentrations, treatment times, temperatures and agitations is being evaluated as alternative and appropriate methods instead of halogenated solvent extraction system. These methods consist of recovery steps followed by incubation, centrifugation and purification steps using ethanol and water washing. The results of this study were compared with PHA extraction from recombinant Cupriavidus necator as a control. The PHA recovered under the most favourable conditions was further characterized. The chemical-free aqueous solution method as a clean process and low concentration of NaOH treatment were successfully developed for PHA extraction from wild type Comamonas sp. EB172. More than 88% purity and 96% recovery yield of PHA were achieved by incubating the wild type bacteria under the mild alkaline treatment using 0.05 M NaOH at 4°C for 1 h. However, up to 96% purity and recovery yield can be obtained by incubation of recombinant C. necator with 0.05 M NaOH at 4°C for 3 h. The incubation of Comamonas sp. EB172 in the chemical-free aqueous solution at 30°C for 5 h could efficiently extract the PHA with more than 93% of recovery yield. Besides, shorter incubation time is required for PHA extraction from recombinant strain using the non-chemical method, which resulted in a PHA with 80.6% of purity and recovery yield of 96.1%. Protein determination and transmission electron microscopy images as well as gas chromatography analysis proved that improvement in cell wall permeability and cell membrane breakage are the possible mechanisms of NaOH treatment and chemical-free aqueous solution method on PHA recovery which was accompanied by considerable release of protein after the extraction step. It was found that the effectiveness of chemical and non-chemical treatments depends on the microbial strain. The initial intracellular PHA content also affected the effectiveness of the extraction methods for PHA recovery. Although, the NaOH treatment could recover purer PHA as compared to the chemical-free method, both processes were able to extract the polymer with high yield. The chemical-free aqueous solution method was found to be better than NaOH treatment for PHA extraction in respect of the final polymer molecular weight, which is in fact almost double that of the chloroform-extracted PHA as control. The overall results in this study indicated that the mild NaOH treatment and the chemical-free aqueous solution methods developed can serve as alternative recovery methods with high potential instead of the conventional halogenated solvent extraction process such as chloroform, since these new methods are environmentally more benign, effective and simple in operation. The recovery of intracellular PHA from Comamonas sp. EB172 cells via the recovery methods developed herein can contribute towards the sustainable process of PHA production using organic acids derived from the anaerobic treatment of palm oil mill effluent (POME).